微小型齿轮加工技术 - 石文天; 刘玉德; 方泽平; 李银宾 (Jixie chuandong)
Micro gear is an important part and the processing technology of micro gear is the key in MEMS.The manufacturing technology of micro gear including LIGA and quasi-LIGA,WEDM,micro plastic forming,micro etching method,micro cutting technology etc is presented.The result of micro gear processed by the technology is introduced and the advantage and shortcoming of the technology is analyzed.Micro cutting in forming micro gear is divided into the two ways such as micro forming milling and micro hobbing technology.Micro forming milling is a forming technology and micro hobbing is a generating method in processing micro gear.Contrasted with the other technology,the generating method used in hobbing process is better than the other methods because of the high quality,low cost,high efficiency,and can adopt with many kind of material of micro gear.Micro hobbing process is a good technology for the flexible batch processing of micro gear.